1997
DOI: 10.1016/s0007-0785(97)80120-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high potencies of tumour necrosis factor alpha on H2O2 production in cultured neuroblastoma cells by enhanced luminol-dependent chemiluminescence (ECL)

Abstract: The effects of homoeopathic high dilutions of cytokine TNFα on H2O2 production of SK-N-SH neuroblastoma cells were studied. H2O2 was measured using a highly sensitive chemiluminescence method (ECL) based on chemical enhancement of luminol oxidation in the presence of peroxidase and H2O2. The dose-effect relationship between TNFα and H2O2 production of SK-N-SH cells was established over the whole range from 200 ng/ml of TNFα to 100x. Interpolation yielded a waveshaped curve (phase length 5–8) which appeared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Furthermore, remedy (0712–2) differed from 0712–3 significantly for the dilutions 1:10 and 1:100 (p < 0.01 and p < 0.001, respectively). It was surprising, that the substance 0712–1 (succussed solvent) caused a modest enhancement on cell motility, but it was already observed that a succussed solvent exerted biological effects [30]. In spite that we did not find any proliferation effect of substances 0712–1 and 0712–2, the NIH 3T3 cells exposed to these substances showed an increasing migration.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, remedy (0712–2) differed from 0712–3 significantly for the dilutions 1:10 and 1:100 (p < 0.01 and p < 0.001, respectively). It was surprising, that the substance 0712–1 (succussed solvent) caused a modest enhancement on cell motility, but it was already observed that a succussed solvent exerted biological effects [30]. In spite that we did not find any proliferation effect of substances 0712–1 and 0712–2, the NIH 3T3 cells exposed to these substances showed an increasing migration.…”
Section: Resultsmentioning
confidence: 53%
“…It has been reported, that compounds at high dilutions/low concentrations could exert different biological activity. TNF-α up to 100x from 100 ng/ml elevated the level of H 2 O 2 in SK-N-SH neuroblastoma cells [30], arsenic of decimal and centesimal dilutions exerted effect in the rats [41], histamine dilutions ranging between 15-19c from 1 mg/ml inhibited human basophil degranulation [42]. In addition, normal and human leukemia T-lymphocytes responded to cadmium chloride at low doses (nM-μM; 0.2-200 ng/ml) [43].…”
Section: Resultsmentioning
confidence: 99%
“…19,20 These studies, however, cannot directly be compared with the current study because they were performed with high potencies of cytokines (␣-interferon respectively tumor necrosis factor-␣), and thus transcend the isopathic model. High homeopathic potencies carry nonmolecular information that can only be understood by an organism or by isolated cells in a given framework.…”
Section: A Discussionmentioning
confidence: 98%
“…The latter gives more stable results. 17,18 In this case, considering all the experiments performed in a study is crucial. The convergence of results is an useful criterion to discriminate non-specific contaminant-related effects of succussed solvent from specific test-substance effects of homeopathic preparation.…”
Section: Methodological Qualitymentioning
confidence: 99%